2014
DOI: 10.5713/ajas.2013.13817
|View full text |Cite
|
Sign up to set email alerts
|

Factor Analysis of Linear Type Traits and Their Relation with Longevity in Brazilian Holstein Cattle

Abstract: In this study we aimed to evaluate the reduction in dimensionality of 20 linear type traits and more final score in 14,943 Holstein cows in Brazil using factor analysis, and indicate their relationship with longevity and 305 d first lactation milk production. Low partial correlations (−0.19 to 0.38), the medium to high Kaiser sampling mean (0.79) and the significance of the Bartlett sphericity test (p<0.001), indicated correlations between type traits and the suitability of these data for a factor analysis, af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 23 publications
(35 reference statements)
0
10
0
Order By: Relevance
“…Thus, the linear classification of type traits becomes an important tool in the decision making process in the herds, as it aims to select animals that express phenotypic traits which will give greater productive life in the herd ( Pérez-Cabal and Alenda, 2002 ; Posadas et al, 2008 ) through their improved productive and reproductive potential. Kern et al (2014) studied the relationship between linear type traits and longevity of cows through factor analysis and reported that selection based on the final score together with the traits related to mammary system (cows with deep, wide, soft, elastic udder, with strong central ligament, cows with good bone quality) would result in more functional cows and consequently with higher MY and productive life in the herd.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the linear classification of type traits becomes an important tool in the decision making process in the herds, as it aims to select animals that express phenotypic traits which will give greater productive life in the herd ( Pérez-Cabal and Alenda, 2002 ; Posadas et al, 2008 ) through their improved productive and reproductive potential. Kern et al (2014) studied the relationship between linear type traits and longevity of cows through factor analysis and reported that selection based on the final score together with the traits related to mammary system (cows with deep, wide, soft, elastic udder, with strong central ligament, cows with good bone quality) would result in more functional cows and consequently with higher MY and productive life in the herd.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the observed covariance structure, the objective of FA is to replace n measured variables with p (p < n) F, where the measured variables are expressed as linear functions of the F, and the F capture the underlying latent concept that the original variables represent (Bollen, 2014). In dairy cattle, the potential use of F obtained from FA has been investigated for a variety of traits, including milk quality, milk technological properties [e.g., MCP and CY-related phenotypes (Macciotta et al, 2012)], type traits (Kern et al, 2014), as well as milk fatty acids (Conte et al, 2016;Mele et al, 2016). However, previous studies were focused on the sources of variation related to the F and their genetic parameters.…”
Section: Introductionmentioning
confidence: 99%
“…This region’s climate has a high potential for forage production. Still, high temperatures, humidity, and intense solar radiation affect the farmer’s ability to maintain balanced milk production throughout the year [ 1 ], as the climate affects the productivity and longevity of dairy cows [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%